2023
DOI: 10.3390/agronomy13061568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Apatite Concentrate in Combination with Phosphate-Solubilizing Microorganisms on the Yield of Ryegrass Cultivar Izorskiy

Abstract: Soil microorganisms play a vital role in increasing the availability of phosphorus (P) for plants through mineralization of organic P and solubilization of precipitated P compounds. In this two-year study, we analyzed several P-solubilizing microorganisms (PSMs) of the genus Bacillus and their consortiums for the ability to release soluble P from apatite concentrates of various grinding degrees using ryegrass (Lolium multiflorum Lam.) as a model plant. The effects were accessed by analyzing plant growth and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Halophytic plants are the best model for the isolation of bacterial endophytes helping with the elimination of excess salt concentrations [ 43 , 44 , 45 , 46 , 47 ]. Many bacteria of the genus Bacillus are able to stimulate plant growth and provide protection under biotic and abiotic stresses [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Halophytic plants are the best model for the isolation of bacterial endophytes helping with the elimination of excess salt concentrations [ 43 , 44 , 45 , 46 , 47 ]. Many bacteria of the genus Bacillus are able to stimulate plant growth and provide protection under biotic and abiotic stresses [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marrocos tem as maiores reservas de fosfato bruto, e as maiores também foram criadas na China (45% da produção total de fosfato, 2018), nos EUA e na Rússia (TIMOFEEVA et al, 2023).…”
Section: Use Of Apatite Concentrate In Soil Managementunclassified
“…Os mesmos autores, avaliaram a eficiência agronômica em milho e também relataram crescimento semelhante em plantas adubadas com fontes naturais de fósforo e fertilizantes fosfatados solúveis. Timofeeva et al (2023) em um estudo de dois anos, analisou o uso de apatita combinado com vários microrganismos solubilizadores de P do gênero Bacillus para produção de azevém (Lolium multiflorum). Os autores relataram que o uso de concentrados de apatita incrementou o crescimento de azevém, porém a combinação do concentrado de apatita com microrganismos solubilizadores de P pode substituir fontes de P solúvel.…”
Section: Use Of Apatite Concentrate In Soil Managementunclassified
“…The genome analysis of strain BS89 revealed the presence of gene clusters responsible for the synthesis of plant-growth-promoting metabolites (indole 3-acetic acid [IAA] and volatiles), numerous hydrolytic enzymes, vitamins, and antimicrobial compounds (surfactin, fengycin, bacilysin, macrolactin, difficidin, bacillaene, and plantazolicin) [27]. It was also demonstrated that strain Bacillus velezensis BS89 can enhance the assimilation of minerals such as Ca and P [28].…”
Section: Introductionmentioning
confidence: 99%